2016
DOI: 10.1002/ece3.2413
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variability and population dynamics: do European and North American ducks play by the same rules?

Abstract: Density dependence, population regulation, and variability in population size are fundamental population processes, the manifestation and interrelationships of which are affected by environmental variability. However, there are surprisingly few empirical studies that distinguish the effect of environmental variability from the effects of population processes. We took advantage of a unique system, in which populations of the same duck species or close ecological counterparts live in highly variable (north Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The size of duck populations vary naturally in response to environmental variation (Pöysä et al 2016) and reproductive output (constrained by nest success and duckling survival), in addition to female survival, are prime vital rates that affect population growth rate (Hoekman et al 2002;Coluccy et al 2008). Ducks represent a group of popular quarry species, for which the harvest is a major contributory source of mortality (Cooch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The size of duck populations vary naturally in response to environmental variation (Pöysä et al 2016) and reproductive output (constrained by nest success and duckling survival), in addition to female survival, are prime vital rates that affect population growth rate (Hoekman et al 2002;Coluccy et al 2008). Ducks represent a group of popular quarry species, for which the harvest is a major contributory source of mortality (Cooch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Even with the use of a PBR-calculated value at prudence recovery factor f = 0.1, our ASMM showed that the population will decrease by 47% in 30 years ( Figure 2D and Table S3), which qualifies such a population as regionally 'Vulnerable' (VU), and very close to regionally 'Endangered' (EN) according to IUCN criteria, which is also not an optimistic forecast. PBR probably works best for populations exhibiting a high degree of density-dependence, while dynamics of many waterfowl populations is driven mainly by environmental variation (Pöysä et al 2016, see also O'Brien et al 2017 for more discussion). Forecasts for the coming years using bycatch values estimated in this article also do not look too optimistic.…”
Section: Discussionmentioning
confidence: 99%
“…Without detailed knowledge of the form of densitydependence, this would result in undue proliferation of possible scenarios. Still, importance of density-dependence for duck population dynamics is debatable (Lawrence et al 2013, Pöysä et al 2016.…”
Section: Age-structured Matrix Population Modelmentioning
confidence: 99%
“…Our data of lake-specific breeding numbers of black-headed gull and other waterbird species are from five regions in southern and central Finland and cover the period of 1977-2017, with the length of the lake-specific time series of breeding numbers varying from 22 to 41 years (Supplementary material, Table A1; additional details for four of the study regions can be found in Pöysä et al, 2016). The lakes in the study regions represent typical lakes in boreal Northern Europe, ranging from oligotrophic lakes surrounded by forest and peat shores to eutrophic lakes surrounded by arable lands.…”
Section: Bird Datamentioning
confidence: 99%